A humanized knockin mouse model of Duchenne muscular dystrophy and its correction by CRISPR-Cas9 therapeutic gene editing - Yu Zhang; Hui Li; Takahiko Nishiyama; John R. McAnally; Efrain Sanchez-Ortiz; Jian Huang; Pradeep P.A. Mammen; Rhonda Bassel-Duby; Eric N. Olson (Elsevier, 2022)
Duchenne muscular dystrophy (DMD) is a lethal neuromuscular disease caused by mutations in the X-linked dystrophin (DMD) gene. Exon deletions flanking exon 51, which disrupt the dystrophin open reading frame (ORF), represent one of the most common types of human DMD mutations. Previously, we used clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated proteins (Cas) gene editing to restore the reading frame of exon 51 in mice and dogs with exon 50 deletions. Due to genomic sequence variations between species, the single guide RNAs (sgRNAs) used for DMD gene editing are often not conserved, impeding direct clinical translation of CRISPR-Cas therapeutic gene-editing strategies. To circumvent this potential obstacle, we generated a humanized DMD mouse model by replacing mouse exon 51 with human exon 51, followed by deletion of mouse exon 50, which disrupted the dystrophin ORF. Systemic CRISPR-Cas9 gene editing using an sgRNA that targets human exon 51 efficiently restored dystrophin expression and ameliorated pathologic hallmarks of DMD, including histopathology and grip strength in this mouse model. This unique DMD mouse model with the human genomic sequence allows in vivo assessment of clinically relevant gene editing strategies as well as other therapeutic approaches and represents a significant step toward therapeutic translation of CRISPR-Cas9 gene editing for correction of DMD.